Influence of Genetic Admixture Components on CYP3A5*3 Allele-Associated Hypertension in Amerindian Populations From Northwest Mexico - Galaviz-Hernández, Carlos; Lazalde-Ramos, Blanca P.; Lares-Assef, Ismael; Macías-Salas, Alejo; Ortega-Chavez, Margarita A.; Rangel-Villalobos, Héctor; Sosa-Macías, Martha (Frontiers in Pharmacology, 2020)
CYP3A5 metabolizes endogenous substrates and 30% of prescription drugs. The CYP3A5 gene contains an active CYP3A5*1 allele, and a non-functional version, the CYP3A5*3 (rs776746), with consequences for drug therapeutic responses and side effects. Both CYP3A5*1 and *3 have been associated with hypertension. The frequency of CYP3A5*3 varies between populations of different ancestries, with Europeans having the highest allele frequency (> 90%). Given the importance of CYP3A5*3 in drug response and hypertension development, the aim of the present study was to evaluate the frequency of this polymorphism and its association with hypertension in vulnerable indigenous populations in Mexico. A total of 372 subjects were recruited from eight ethnic groups in Northwest Mexico. Systolic (SBP), diastolic (DBP), and median (MBP) blood pressures as well as body mass index (BMI) were measured. Ancestry was evaluated through STR analysis, and the CYP3A5*1/*3 polymorphisms were identified using real-time PCR with TaqMan® probes. Higher frequencies of CYP3A5*1 and *3 were observed in groups with higher (>90%) and lower (<90%) Amerindian ancestry, respectively. The CYP3A5*3/*3 genotype was more frequent in indigenous women with higher SBP and DBP values. On the other hand, the *1 allele showed a protective effect against both high SBP (OR, 0.38; 95% CI, 0.17–0.83, p = 0.001) and DBP (OR 0.38, 95% CI 0.18–0.81, p = 0.007) in women. This association remained significant after adjusting for BMI and age for diastolic (OR, 0.38; 95% CI, 0.17–0.84, p = 0.011) and systolic BP (OR, 0.33; 95% CI, 0.15–0.76, p = 0.005) BP levels in women. Thus, the frequency of CYP3A5*3 varies between groups and seems to depend on ancestry, and CYP3A5*1 decreases the risk of hypertension in Mexican indigenous women. This population analysis of CYP3A5*1/*3 has profound implications not only for the susceptibility to diseases, such as hypertension, but also for safer drug administration regimens, assuring better therapeutic responses and fewer side effects.